Modernism à la mode : fashion and the ends of literature - Sheehan, Elizabeth M. (Cornell University Press, 2018)
"This book puts the work of early twentieth-century texts in conversation with twenty-first-century theories of affect, materiality, animality, beauty, and history and explores how fashion describes the limits and possibilities for modernist aesthetic and political transformation"-- Provided by publisher.
Keywords: English fiction -- 20th century -- History and criticism.; American fiction -- 20th century -- History and criticism.; Fashion in literature.; Modernism (Literature) -- Great Britain.; Modernism (Literature) -- United States.; Roman anglais -- 20e siècle -- Histoire et critique.; Roman américain -- 20e siècle -- Histoire et critique.; Modernisme (Littérature) -- Grande-Bretagne.; Modernisme (Littérature) -- États-Unis.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; DESIGN -- Fashion.; American fiction; English fiction; Fashion in literature; Modernism (Literature); Great Britain; United States; 1900-1999; Criticism, interpretation, etc.